Large-scale preparation of β-1, 2-glucan using quite a small amount of sophorose. Issue 10 (3rd October 2019) - Kobayashi, Kaito; Nakajima, Masahiro; Aramasa, Hiroki; Kimura, Satoshi; Iwata, Tadahisa; Nakai, Hiroyuki; Taguchi, Hayao
ABSTRACT: A large amount of β-1, 2-glucan was produced enzymatically from quite a small amount of sophorose as an acceptor material through three synthesis steps using a sucrose phosphorylase and a 1, 2-β-oligoglucan phosphorylase. The first synthesis step was performed in a 200 μL of a reaction solution containing 5 mM sophorose and 1.0 M sucrose. β-1, 2-Glucan in a part of the resultant solution was hydrolyzed to β-1, 2-glucooligosaccharides by a β-1, 2-glucanase. The second synthesis was performed in 25 times the volume for the first synthesis. The hydrolysate solution (1% volume of the reaction solution) was used as an acceptor. After treatment with the β-1, 2-glucanase again, the third synthesis was performed 200 times the volume for the second synthesis (1 L). The reaction yield of β-1, 2-glucan at each synthesis was 93%, 76% and 91%. Finally, more than 140 g of β-1, 2-glucan was synthesized using approximately 20 μg of sophorose as the starting acceptor material. Abbreviations: DPs: degrees of polymerization; SOGP: 1, 2-β-oligoglucan phosphorylase; Sopn s: β-1, 2-glucooligosaccharides with DP of n; Glc1P: α-glucose 1-phosphate; SucP: sucrose phosphorylase from Bifidobacterium longum subsp. longum ; SGL: β-1, 2-glucanase; Ca SGL: Chy400_4174 protein; TLC: thin layer chromatography; GOPOD: glucose oxidase/peroxidase; PGM: phosphoglucomutase; G6PDH: glucose 6-phosphate dehydrogenase Graphical abstract: : β-1, 2-Glucan was synthesized by repetition of elongation and degradation of the β-1, 2-glucan using only a small amount of sophorose.